Tradisi Salai Jin Sebagai Modal Sosial Masyarakat Tidore Kepulauan - Yusri A Boko; Jamin Safi (Universitas Galuh, 2023)
The Tidore people are people who still adhere to the traditions passed down by their ancestors. One of the traditions in question is the Salai Jin ritual. Viewed from the aspect of social relations, this tradition characterizes social interaction between people. The Salai Jin ritual is basically a ritual which, according to local people's beliefs, allows communication between humans and supernatural beings with various purposes. Among the purposes of this ritual is to establish cooperation to ensure safety and health. The researcher is interested in examining (1) the values of the Salai Jin ritual as one of the social assets of the Tidore archipelago community, and (2) the meaning and internalization of the values of the Salai Jin ritual in the social life of the Tidore archipelago community. Designed as a descriptive qualitative research, data were collected through interviews, observation, and documentation. Meanwhile, triangulation is used to validate research data. After the data has been analyzed using data reduction techniques, data presentation, and drawing conclusions, this study captures several social phenomena related to the Salai Jin ritual in the Tidore Islands community, including, (1) the Salai Jin ritual contains values of togetherness, bari (mutual cooperation), empathy, and social care, and (2) the meaning of these values is to build good communication and cooperation based on the values and norms prevailing in society. The actualization of the Salai Jin ritual as social capital can be found in various mutual cooperation activities such as building houses, wedding celebrations, dina (the tradition of commemorating those who have died), and other community social activities.